Extraction of Cork Fish Bone Gelatin (Channa striata) with Different Acid Variations in the Demineralization Process - Jaya, Fitra Mulia; Rochyani, Nenny (Jurnal Perikanan dan Kelautan, 2020)
Palembang is the capital city of South Sumatra Province which has special foods which main raw material is fish. Many pempek entrepreneurs use cork fish meat for pempek raw material resulting in abundance of cork fish bone waste, therefore researchers utilize cork fish bone waste as an alternative into raw material in making gelatin. In this study, researchers used several weak acids derived from natural ingredients such as lime extract and starfruit extract and as a comparison researchers used synthetic weak acids namely citric acid in the market. The purpose of this research used several types of acids in the demineralization process to produce better gelatin production. This study used a Completely Randomized Design, with several acid treatments with and consisting of 3 (three) treatment levels, each treatment was repeated 3 times. The treatment in this study was a demineralization process with the addition of citric acid was (A1), lime extract was (A2), and starfruit extract was (A3). The parameters examined in this study include: Gelatin yield, Gelatin acidity (pH), Moisture and Sensory content (color and aroma). Data from proximate observations were analyzed by analysis of variance (ANOVA) and further tested based on the coefficient of diversity. From the results of this study, it was found that the best treatment of using variations in acid was gelatin demineralized using citric acid which produced a yield was 6%, a moisture content was 9.21%, pH 6, the panelist's favorite value of color was 4.3 and aroma 3, 8